EFFECT OF ORGANOPHOSPHATE PESTICIDE MALATHION ON IN-VITRO OOCYTE MATURATION, FERTILIZATION AND EMBRYO DEVELOPMENT OF NILI RAVI BUFFALO (BUBALUS BUBALIS) - F. Aziz; Z. Mehboob; S. Jalali; S. A. Shami; I. Z. Qureshi (Journal of Animal and Plant Sciences, 2012)
The present study evaluated in-vitro toxicity of organophosphate insecticide, malathion on nuclear maturation, fertilization and subsequent embryo development of the oocytes obtained from abattoir ovaries of Nili-Ravi Buffalo (Bubalus bubalis). The cumulus-oocyte complexes (COCs) in culture medium were exposed to four different regimens of malathion, 1.56 µmol, 3.12 µmol, 6.25 µmol and 12.5 µmol. Results demonstrated dose dependent significant difference (P < 0.05) in nuclear competence, oocyte maturation and degeneration. Cumulus expansion showed significant increase (P < 0.05) while oocyte diameter increased non significantly (P > 0.05). The COCs that attained nuclear maturation (MII) and were subjected to IVF and, subsequent embryonic development also showed dose dependent non-significant (P > 0.05) decrease in fertilization and embryonic development, however, hatched blastocyst formation was significantly compromised (P < 0.05). The blastocyst development with inner cell mass was again non- significantly different (P > 0.05). The study concludes that malathion may effect quality of preimplantation embryos developed in-vitro from immature oocytes pre-exposed to the pesticide.
Keywords: Malathion; organophosphorous insecticides; in-vitro maturation; buffalo oocytes